A novel multikinase inhibitor SKLB‐YTH‐60 ameliorates inflammation and fibrosis in bleomycin‐induced lung fibrosis mouse models. (14th June 2021) - Liu, Hongyao; Wu, Xiuli; Gan, Cailing; Wang, Liqun; Wang, Guan; Yue, Lin; Liu, Zhihao; Wei, Wei; Su, Xingping; Zhang, Qianyu; Tan, Zui; Yao, Yuqin; et al.
Abstract: Objectives: Idiopathic pulmonary fibrosis (IPF) is marked by the excessive accumulation of extracellular matrix, which participates in a variety of chronic diseases or injuries and seriously threatens human health. Due to the side effects of clinical drugs, there is still a need to develop novel and less toxic drugs to treat pulmonary fibrosis. Materials and Methods: SKLB‐YTH‐60 was developed through computer‐aided drug design, de novo synthesis and high‐throughput screening. We employed the bleomycin (BLM)‐induced lung fibrosis animal models and used TGF‐β1 to induce the epithelial‐mesenchymal transition (EMT) of A549 cells in vitro. Meanwhile, the protein expression of collagen I and the α‐smooth muscle actin (α‐SMA), E‐cadherin, p‐FGFR1, p‐PLCγ, p‐Smad2/3 and p‐Erk1/2 was detected by western blot. Results: YTH‐60 has obvious anti‐proliferative activity on fibroblasts and A549 cells. Moreover, YTH‐60 could impair the EMT of A549 cells and suppressed fibrosis by inhibiting FGFR and TGF‐β/Smad‐dependent pathways. Intraperitoneal administration of preventive YTH‐60 could significantly reduce the degree of fibrosis in mice and regulate the imbalance of the immune microenvironment. In addition, we observed that therapeutic YTH‐60 treatment attenuated fibrotic changes in mice during the period of fibrosis. Importantly, YTH‐60 has shown an acceptable oral bioavailability ( F = 17.86%) and appropriate eliminated half‐life time ( T 1/2 = 8.03 hours). Conclusions: Taken together, these preclinical evaluations suggested that YTH‐60 could be a promising drug candidate for treating IPF. Abstract : Schematic model for anti‐fibrotic activity of SKLB‐YTH‐60. In vitro YTH‐60 inhibits the activation of fibroblasts and the EMT of epithelial cells induced by TGFβ1. Intraperitoneal injection of YTH‐60 not only inhibits the bleomycin‐induced lung inflammation, regulates the lung immune microenvironment, but also prevents and reverses pulmonary fibrosis. Finally, the anti‐fibrosis effect of YTH‐60 may be via inhibiting of FGFR and TGF‐β/Smad signaling pathway.